Empowering Kindergarten Teachers: The Role of Online Business in Enhancing Economic Well-being at Yayasan Chalisarurrahmi Luqman Halim, Medan - Kartika Sari Lubis; Ade Rahma Ayu; Vidya Fathimah; Desy Irana Dewi Lubis (PT Katersi Minar Permata, 2024)
Kindergarten teachers play a crucial role in early childhood education, which is the foundation for children's intellectual, social, and emotional development. However, their economic welfare is often overlooked, with many kindergarten teachers receiving inadequate salaries. This can affect their quality of life and the quality of education they provide. Low economic welfare can lead to stress, decreased motivation, and impact their performance at work. Time and resource constraints often hinder kindergarten teachers from seeking additional income, as most of their time is spent teaching and preparing learning materials. Furthermore, many kindergarten teachers lack the knowledge or skills to start a side business. Online business offers a solution with the flexibility to run a business without leaving their main job. With relatively low capital requirements and technological advancements providing access to a global market, online business becomes a feasible alternative to increase the income of kindergarten teachers. Therefore, socialization regarding the importance of online business can significantly benefit the economic welfare of kindergarten teachers, providing them with opportunities to leverage digital-era advantages through social media.